Eating behavioral reactions of patients with chronic non-communicable diseases and its correction - Shalimova, Anna; Isayeva, Ganna; Vovchenko, Maryna; Rieznik, L.; Buriakovska, Olena; Emelyanova, N. (My University, 2019)
The peculiarities of the eating behavioral reactions of patients with chronic non-communicable diseases and the effect of group and individual therapy on them were evaluated. It was established, that with a tendency to positive changes in eating behavior, conducting both group and individual therapy for 1 year did not significantly change its indicators such as daily consumption of salt, vegetables and fruits, smoking and alcohol consumption, which confirms the complexity of the impact on the specified risk factor for the development and progression of chronic non-communicable diseases.
Keywords: eating behavior; individual therapy; chronic non-communicable diseases; group therapy